Effect of sexual rest in buck and changes in maternal behavior on litter performance - Nur Shahida Nafisah Buhaira (2022)
The potential of rabbit industry is emerging, and number of breeders elevated recently. Optimization on rabbit production rely on proper breeding management. Bucks with best performance are preferred and mated frequently promises best quality and highest litter seize. However, repetitive services of buck may lead to sexual exhaustion and low conception rate in doe. To our knowledge, information on the effect of sexual rest buck on does and litter performance are lacking. The study aimed a) to determine the effect of different days of sexual rest in the buck on doe’s conception rate. b) to investigate the maternal effect and post-maternal behaviors on litter performance. A total of eight does with 4 bucks (New Zealand White) performed natural mating. Rabbits were divided into two groups (G1 and G2) where males were given one day and three days of sexual rest before natural mating. Effect in different days of sexual rest for buck on doe’s conception rate and the influence of maternal effect and post-maternal behaviors on litter performance were observed. Result showed that there is no significant difference in different days of sexual rest given in buck on doe’s conception rate (p value= 0.356). For post maternal analysis, there is significant difference in doe’s body weight changes due to pregnancy (p value= 0.04). Moreover, positive correlation (r= 0.67) was confirmed between gestation period with litter size at birth was reported. Plus, positive correlation (r= 0.1615) was observed between nest-building behaviors and kits born alive after 1 week. In conclusion, there is no significant differences on conception date and post maternal for different days of sexual rest on buck. Future work on semen quality would improve the current finding.